3(3x+3)=-5(5x-5)-3x

Simple and best practice solution for 3(3x+3)=-5(5x-5)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+3)=-5(5x-5)-3x equation:



3(3x+3)=-5(5x-5)-3x
We move all terms to the left:
3(3x+3)-(-5(5x-5)-3x)=0
We multiply parentheses
9x-(-5(5x-5)-3x)+9=0
We calculate terms in parentheses: -(-5(5x-5)-3x), so:
-5(5x-5)-3x
We add all the numbers together, and all the variables
-3x-5(5x-5)
We multiply parentheses
-3x-25x+25
We add all the numbers together, and all the variables
-28x+25
Back to the equation:
-(-28x+25)
We get rid of parentheses
9x+28x-25+9=0
We add all the numbers together, and all the variables
37x-16=0
We move all terms containing x to the left, all other terms to the right
37x=16
x=16/37
x=16/37

See similar equations:

| n^2-48=-2n | | (120/8)=(17/x) | | 9x-4=2x+94 | | -83-7x=-15x+5 | | -7-4x=-5x+6 | | -8(x+1)=-5x-35 | | 4x+5=6x-6 | | 2(5x+4)=-5(5x-4) | | 8y=8+6y | | 28-4x=15+9x | | x+7=5x-53 | | 1/2(x+5)-4=1/3=(2x-1) | | -7(2r-1)+3(8-r)=0 | | 5x-8(x+5)=√3-3x | | n÷9=4 | | x=2.62=6.37 | | −48−7n=9n−5(4n+8) | | h+(h+6)+4(h+6)=126 | | 16=8x+1-5 | | -(z+5=-14 | | 8x-10/5=2 | | -18=3(v-4)-6v | | 12k-50=2(2k)+2(3) | | 5x+7x-9=3(4x+8) | | 4x-36=-5x | | -10x-19=-5x+26 | | 2x-8-4x=6x+9x+4 | | 2z+6z-451=2485 | | 30=6x-42 | | (x-5)/3=5/6 | | x/20-x/16=-1/10 | | -2p+6p=-8(6+4p)-8(-4p+2) |

Equations solver categories